A survey of parallel numerical methods for initial value problems for ordinary differential equations - Jackson, K.R. (IEEE transactions on magnetics, 1991)
The parallel solution of initial value problems for ordinary differential equations has become an active area of research. Recent developments in this area are surveyed with particular emphasis on traditional forward-step methods that offer the potential for effective small-scale parallelism on existing machines.< >